O processo de comunicação científica no campo da Defesa no Brasil: da geração do conhecimento à disponibilização da informação - (:unkn) unknown (Instituto Brasileiro de Informação em Ciência e Tecnologia/Universidade Federal do Rio de Janeiro, 2015)
This research theme is the scholarly communication in the academic-scientific field of national defense. This is an exploratory study that identified and analyzed the scientific productivity of teachers included in the programs of post graduate Political Science and International Relations, with areas of concentration and lines of research in defense and security in Brazil, in the triennium 2010 -2012. A qualitative and quantitative analysis of the technical-scientific productivity of teachers was held from the count of items per year; by type of publication and program; the authorship pattern; endogeny and publication in foreign communication channels. The Graduate Program in International Relations San Tiago Dantas distinguished by significant scientific output, followed by the UNB program. But the PUC-Rio program had more than half (51%) of their publications in journals QUALIS A and the same percentage in foreign publications channels. Among the features of the scientific production, the preferred communication channels for the dissemination of research results are the book chapters and journal articles, on equal terms; the authorship pattern is the individual publication and publications in foreign communication channels do not constitute a habitus of the field. This research revealed, among the 90 teachers of the programs, the 20 most productive. The average is 8 articles by authors in three years, which means 2.6 annual average, by author, index satisfactory. There are three highlighted themes: Foreign and Regional Integration, with 25% attendance; Globalization, governance and development, with 17% attendance; and International Political Economy, with 13%. This research found that there is no consensus on the concept of defense, nor about which area should be hierarchically linked. For the occurrence of institutionalization of Defense as area of knowledge, become urgent political efforts, especially of science policy, technology and innovation, and how, in order to gain space on the scene. The results show a significant production during the construction field. The area Defense incipient as a field of knowledge, needs to demonstrate its growth potential through the results and presenting the progress made to date.
Keywords: Produtividade Científica; Comunicação Científica; Ciência da Informação; Defesa Nacional; Scientific Productivity; Scholarly Communication; Information Science; National Defense; CNPQ::CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO